Knowledge-driven actions; Transforming higher education for global sustainability: Independent Expert Group on the Universities and the 2030 Agenda - Davies, Anna (UNESCO, 2022)
Universities and, more broadly, higher education institutions (HEIs), need to use the knowledge they produce and their education of new professionals, to help solve some of the world ́s greatest problems, as addressed by the Sustainable Development Goals (SDGs) set out by the United Nations (UN). Humanity is facing unprecedented challenges, most strikingly so in relation to climate change and loss of nature and biodiversity, as well as inequality, health, the economy, and a suite of issues related to the 2030 Agenda. Given this new reality in which the future of humans, along with other species, is at stake, it is time for HEIs and their stakeholders to systematically rethink their role in society and their key missions, and reflect on how they can serve as catalysts for a rapid, urgently needed and fair transition towards sustainability. The complexity of the issues at stake means that solutions should be part of a radical agenda that calls for new alliances and new incentives. It is also time for HEIs to make sustainability and SDG literacy core requisites for all faculty members and students. Sustainability education should bring students into contact with real-world problems and immersive experiences. Appreciating the greater good of both people and planet, and contributing to values beyond mere monetary gain will further enthuse and inspire students and faculty mentors alike. Ultimately, the educational culture at universities and HEIs needs to encourage students to learn via experimentation and critical thinking from multiple perspectives. This report is undoubtedly about the SDGs; however, it is important to realize that these will expire in 2030. We thus strongly recommend that HEIs, while being a part of that agenda, should also look ahead – not only to implementing the SDGs, but also to being intensively involved in crafting the next steps and goals beyond 2030. A long-term perspective needs to be adopted for both HEI activities and policies. The call this report makes is for universities and HEIs to play an active part in an agenda that has the consensus of 193 countries and aims to resolve some of the world’s most pressing problems, as stated in the 17 SDGs. The challenge is for HEIs to embrace the 2030 Agenda, because if they do not it will be difficult, if not impossible, to achieve the SDGs. The SDGs represent a unifying challenge for all universities and HEIs, and this must be reflected in plans and actions for research, education and outreach. HEIs have played a crucial role as bringers of societal enlightenment and change over the centuries, maintaining their role as free and critical institutions while also – to varying degrees – aiming to perform a service within societies. It is essential to maintain and encourage these important roles and enable HEIs to combine their traditions of critical thinking with problem-solving activities, while also adjusting their role in the light of societal changes. The future of humanity and our planet is under threat, and the need for critical thinking and societal change is therefore more pressing than ever. HEIs should inspire societal change when necessary, taking a leading role in the transitions necessary for humankind and emphasizing that the need for change is immediate. This also implies that HEIs should think critically about their own practices, curricula and research, and about how to motivate their employees, students and society at large to do the same. The opportunity for answering the call is now. HEIs, their leaders, faculty and students have specific roles and responsibilities in societal transformation, according to the type of institution and the problems faced. For this purpose, the structure and culture of HEIs have to change, and barriers to the necessary transformations within HEIs must be identified and gradually eliminated. This report focuses on, and advocates, three main areas of HEI transformation: the need to move towards inter- and transdisciplinarity in education and research; the imperative need for institutions to become open, fostering epistemic dialogue and integrating other ways of knowing; and the demand for a much stronger presence in society in general through proactive outreach activities and partnering with other societal actors, in order to build awareness of ecological deterioration and the SDGs in general, and to influence policy. This implies directly intervening in experimental projects that test solutions, with the participation of students. The report deals with some of the systemic barriers that might hinder progress in these three areas of transformation. The recognition of the value of life and the need of all humans for quality of life requires a reaffirmation of the human rights-based approach to the education we give and the research we carry out. This implies recognizing that achieving human rights for all is not possible unless we actively protect our natural resources and all forms of life, and struggle constantly against the power relations that foster inequality and all forms of violence and discrimination. It also implies an appreciation of the value of cultural diversity, recognizing the contribution different cultures can make to progress towards these goals. Equity and inclusion are values that also stand out when embracing the 2030 Agenda; the commitment to leaving no one behind becomes key. The contribution of HEIs is manifold: theoretical, philosophical and, clearly, ethical. It must also be geared to removing barriers towards sustainable societies and the greater well-being of people and planet. The recommendations in the report address the ways in which HEIs – recognizing the very different cultures and contexts within which they have emerged and operate – can move forward towards each of these objectives, and how the existing structural and cultural barriers discussed in the body of the report might be transformed.
Keywords: Smart & Sustainable Planet; SDG; SUSTAINABILITY; sustainability transitions